2009
DOI: 10.1128/mcb.01830-08
|View full text |Cite
|
Sign up to set email alerts
|

H2AX Is Required for Cell Cycle Arrest via the p53/p21 Pathway

Abstract: Phosphorylation of H2AX (␥H2AX) is an early sign of DNA damage induced by replication stalling. However, the role of H2AX in the repair of this type of DNA damage is still unclear. In this study, we used an inactivated adeno-associated virus (AAV) to induce a stalled replication fork signal and investigate the function of ␥H2AX. The cellular response to AAV provides a unique model to study ␥H2AX function, because the infection causes pannuclear H2AX phosphorylation without any signs of damage to the host genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
141
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(150 citation statements)
references
References 58 publications
8
141
1
Order By: Relevance
“…2c), which is involved in apoptosis [18]; p21 (Fig. 2d), involved in the regulation of growth and cellular senescence [20]; and TIGAR (Fig. 2e), involved in apoptosis and the regulation of glucose metabolism [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2c), which is involved in apoptosis [18]; p21 (Fig. 2d), involved in the regulation of growth and cellular senescence [20]; and TIGAR (Fig. 2e), involved in apoptosis and the regulation of glucose metabolism [22].…”
Section: Resultsmentioning
confidence: 99%
“…Activation of p53 triggers upregulation of genes involved in apoptosis, such as PUMA (p53 upregulated mediator of apoptosis; also known as BBC3) and PTEN (phosphatase and tensin homologue) [18,19], and in senescence, such as p21 (also known as CDKN1A) [20], and of its feedback inhibitor, murine double minute oncoprotein (MDM2) [21]. Recently, it has also been shown that p53 regulates glucose metabolism via Tp53-induced glycolysis and apoptosis regulator (TIGAR) [22] and insulin sensitivity via PTEN, the main negative regulator of phosphorylation of the serine/threonine protein kinase AKT [17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, diffuse and pan-nuclear γ H2AX staining has been found to occur upon non-ionizing UV-C irradiation, independent of DNA-DSBs (Marti et al , 2006 ). Infection with inactivated adeno-associated virus has been shown to lead to replication fork stalling and a diffuse γ H2AX nuclear staining, which is essential for subsequent cell-cycle arrest in the absence of DNA damage (Fragkos et al , 2009 ). However, the mechanism behind this diffuse γ H2AX distribution pattern as well as its functional relevance are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The plate was placed in a Hoefer UVC 500 UV cross-linker (Hoefer Inc.) for UV irradiation at a dose of 720 mJ/cm 2 (25,32). To ensure that most of the cells were infected, CrFK cells were infected with the UV-inactivated virus at an MOI of 3 FFU/cell.…”
Section: Virus and Infectionmentioning
confidence: 99%